Offshore Hydrogen, Methanol, and Ammonia Production Review - Otlu, Onur; Yumurtaci, Zehra (MDPI, 2026)
Far offshore wind resources are important for reaching the global renewable energy and decarbonization objectives, but great distances to shore and deep waters preclude underwater electricity lines or traditional turbine or platform foundations. At these distances, converting the produced electricity to hydrogen via electrolysis of purified seawater is attracting interest. This hydrogen can then be transferred with fewer losses via undersea pipelines or transported to shore via ships. The difficulties of storing and transporting hydrogen over large distances can also be remedied by converting it into easily transported e-fuels, such as methanol and ammonia. The paper summarizes the current literature in terms of technologies and strategies involved in these renewable fuel production processes and highlights power consumption, efficiency, and levelized cost figures. These renewable e-fuels promise an environmentally friendly method of tapping into vast overseas resources that can be utilized on shore or provided to sea vessels for refueling. However, electrolyzer, synthesis reactor, and deep-water foundation or floating platform costs need to be brought down significantly by research and development before they can become commercially feasible in the coming decades.
Keywords: offshore; wind; hydrogen; methanol; ammonia; e-fuels; RENEWABLE HYDROGEN; WIND POWER; Energy & Fuels